Prevalensi dan Faktor Risiko Stunting pada Balita di Kelurahan Belawan II Kecamatan Medan Belawan - Dikha Dian Atala; Desy Herawaty Harahap; Surianti Surianti; Cindy Pertiwi; Cindy Salsabila; Derina Derina (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Stunting is a problem of malnutrition in toddlers caused by several factors. Stunting in Indonesia in 2018 increased to 30.8% and 2019 decreased to 27.7% or in other words 28 out of 100 toddlers suffer from stunting. The purpose of this study was to describe the factors that cause stunting in toddlers in Belawan II Village, Medan Belawan District. This type of research is quantitative with a case-control research design, data collection is carried out with primary data and secondary data. Primary data was obtained from the research instrument, namely interviews with mothers in the area, while secondary data was obtained from puskesmas data and local health profile data. The analysis carried out in this study is bivariate analysis with Chi-Square or OR. The results of this study indicate that there is a relationship between parents' work and the incidence of stunting, p-value 0.029. there is a relationship between parental education and the incidence of stunting p-value 0.046. there is a relationship between parental income and the incidence of stunting 0.010. there is a relationship between nutritional status and the incidence of stunting 0.001. there is a relationship between age and the incidence of stunting 0.002. and in this study there was no relationship between latrines 0,119 and water sources 0,054 with the incidence of stunting with (Î±)=0.05).